Upaya Peningkatan Pengetahuan Hidup Bersih Dan Sehat Pada Anak Sekolah Menengah Pertama - Niluh Desy Purnamasari; Sudirman, Sudirman; Parmi, Parmi; Lexy Kareba; Desak Eka Susianawati; Hendrik, Hendrik (Lembaga Dongan Dosen, 2023)
Introduction: Clean and Healthy Behavior (CHB) in school settings plays a pivotal role in preventing diseases, enhancing student health, and fostering a clean and healthy environment. However, CHB implementation in Indonesian schools remains limited, leading to adverse public health effects, including an upsurge in diarrheal cases. Thus, enhancing CHB knowledge and practices in schools is imperative, especially in Central Sulawesi Province, which grapples with a high prevalence of diarrheal cases. Method: This community service initiative took place at SMP Negeri 13 Sigi, Sigi Regency, involving 336 students across different grade levels. Spanning three days in June 2022, the program employed pretest and posttest assessments via questionnaires. Education delivery encompassed material presentations, discussions, and the utilization of electronic and visual aids. Results: Research findings indicate a significant enhancement in students' comprehension of Clean and Healthy Behavior (CHB) following the educational intervention. Previously limited in their understanding, students exhibited noticeable improvements in their knowledge of CHB after participating in the educational activities. These outcomes underscore the vital role of education and outreach in augmenting students' understanding and awareness of CHB. Conclusion: This initiative concludes that educational interventions and outreach efforts pertaining to PHBS in schools can positively impact students' awareness and knowledge of the significance of PHBS. It is anticipated that this heightened awareness will empower students to maintain school cleanliness and improve their health and hygiene practices.